Analisis Kuat Tekan Sulfur Polymer Concrete dari Pemanfaatan Limbah Sulfur Tanpa dan Dengan Proses Pemadatan - Sari, Nur Fajar Aprilia (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The mixture of hydrocarbon compounds in crude oil accounts for 90-95% of the oil's weight, while the remainder consists of non-hydrocarbons such as sulfur, oxygen, nitrogen, and metals. Sulfur in crude oil is removed due to its odor and corrosive properties. If this sulfur waste is not managed properly, it can have negative impacts on the environment. This research aims to analyze the compressive strength behavior of Sulfur Polymer Concrete (SPC) produced without a compaction process and Sulfur Polymer Concrete produced with a compaction process. SPC produced with a compaction process has a higher compressive strength than SPC produced without compaction. This is evident in the A3 variation, where the A3 variation produced with compaction has a compressive strength of 14 MPa, while the A3 variation produced without compaction has a compressive strength of 3.4 MPa. The similarity in the compressive strength of SPC produced without compaction and SPC produced with compaction lies in the pattern where the compressive strength reaches a saturation point. The addition of sulfur increases the compressive strength, and when it reaches its saturation point, the strength decreases with further addition because there is no more aggregate available to be bound, causing the sulfur to solidify.